Internalisasi Karakter Islami Berbasis Kultur Madrasah di Madrasah Aliyah Negeri 4 Bantul - Kamaluddin, Muhammad Anas; Ru'iya, Sutipyo (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
This study aims to describe the internalization of Islamic character building based on madrasah culture in MAN 4 Bantul and the factors that influence the implementation. This research uses a qualitative method with a descriptive approach. The primary data sources in this research are the head of the madrasah, two religious teachers and two students, while the secondary data for this research are books and journals. Data collection techniques are through observation, interviews using purposive sampling techniques, and documentation. Data analysis was carried out through data reduction, data presentation and drawing conclusions. The results of the study indicate that the instillation of Islamic character is carried out through the planning of the School Work Plan, implementation based on madrasah culture (vision, mission, goals, motto, rules, leadership, learning interactions, and student work such as calligraphy and banners of pearls of wisdom), and evaluation through test results, exams, student behavior, and report card grades. Supporting factors include teacher synergy, adequate facilities and infrastructure, and student collaboration between boarding schools, orphanages, and homes, while inhibiting factors are low student motivation, lack of follow-up on character instillation in the home environment, and punishment at the boarding school/orphanage in the morning which causes students to be late to the madrasah.